2011
DOI: 10.1590/s0004-27302011000800018
|View full text |Cite
|
Sign up to set email alerts
|

TSH neurosecretory dysfunction (TSH-nd) in Down syndrome (DS): low risk of progression to Hashimoto's thyroiditis

Abstract: INTRODUCTION: Patients with Down syndrome (DS) often have elevated TSH (hypothalamic origin), which is called TSH neurosecretory dysfunction (TSH-nd). In these cases, there is slight elevation in TSH (5-15 µUI/mL), with normal free T4 and negative thyroid antibodies (AB). OBJECTIVE: To recognize the risk of progression to Hashimoto's thyroiditis (HT). SUBJECTS AND METHODS: We retrospectively analyzed 40 DS patients (mean age = 4.5 years), followed up for 6.8 years. RESULTS: HT was diagnosed in 9/40 patients, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…A recent study demonstrated that the distribution plot for TSH had a significant shift of the curve to higher values in subjects with DS respect to healthy controls, suggesting that hyperthyrotropinemia is an innate attribute of chromosome 21 trisomy [36]. Moreover, some authors [5,37,38] have proposed that S-HT is probably related to inappropriate secretion of TSH or thyroid insensitivity to TSH, rather than to autoimmune thyroiditis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study demonstrated that the distribution plot for TSH had a significant shift of the curve to higher values in subjects with DS respect to healthy controls, suggesting that hyperthyrotropinemia is an innate attribute of chromosome 21 trisomy [36]. Moreover, some authors [5,37,38] have proposed that S-HT is probably related to inappropriate secretion of TSH or thyroid insensitivity to TSH, rather than to autoimmune thyroiditis.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of ATA in DS children was reported to range from 16% [38] to 39% [39]. Moreover, the increased TSH levels were demonstrated to be positively correlated with TPOab which were already indicated as a key factor in the follow-up of DS subjects [40].…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, in another original printing ( 47 ), it was found that DS patients with elevated TSH concentration had low risk of progression to Hashimoto’s thyroiditis—10% for males and 6% for females. Similar conclusions that Hashimoto’s thyroiditis in DS children occurs without female predominance were drawn by Aversa et al ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid dysfunctionespecially the SH pattern, which is commonly observed in very young DS infants-may also be of non-autoimmune etiology, suggesting a congenital thyroid alteration, which is directly related to the trisomy condition of chromosome 21. This phenomenon could be explained by a non-pathological shift in the normal range of TSH as a characteristic of DS, which results in a generally mild and transient form of SH at the group level [65,91,141].…”
Section: Down Syndromementioning
confidence: 99%